Correction: Opposite responses of normal hepatocytes and hepatocellular carcinoma cells to substrate viscoelasticity. (10th March 2020) - Mandal, Kalpana; Gong, Ze; Rylander, Alexis; Shenoy, Vivek B.; Janmey, Paul A.
Abstract : Correction for 'Opposite responses of normal hepatocytes and hepatocellular carcinoma cells to substrate viscoelasticity' by Kalpana Mandal et al., Biomater. Sci., 2020, 8, 1316–1328.